(untitled) (Materiali di Estetica. Terza serie, 2019)
The essay tries to analyze the extraordinary intuitions of Gillo Dorfles about fashion. According to him, fashion is considered an essential starting point to learn contemporary society because it’s the index that disclose our choices, not only about clothes. Every aspect of our live can be judged through fashion. Reading his bibliography and interviews it’s immediately clear that will not be an historical tale, but an intensive social and aesthetics investigation.